а) 3х² + 11х – 4 = ( х + 4) ( 3х - 1 )
б) 16x² + 8х + 1 = (4х + 1)²
5х² + 33х + 40 = 5(х+5)(х-а)
5х² + 33х + 40 = 25х - 25а + 5х² - 5ха
8х + 40 = - 5х ( 5 + а )
5 + а = 8х + 40 / - 5х
а = (8х + 40 / - 5х) - 5
3х²+5х-2 / х² - 4 =
= 3х² + 6х - х - 2 / (х - 2) (х + 2) =
= 3х (х + 2) - (х + 2) / (х - 2) (х + 2) =
= (х + 2)(3х - 1) / (х - 2) (х + 2) =
= (3х - 1) / (х - 2)
Подробное решение во вложении
а) 3х² + 11х – 4 = ( х + 4) ( 3х - 1 )
б) 16x² + 8х + 1 = (4х + 1)²
5х² + 33х + 40 = 5(х+5)(х-а)
5х² + 33х + 40 = 25х - 25а + 5х² - 5ха
8х + 40 = - 5х ( 5 + а )
5 + а = 8х + 40 / - 5х
а = (8х + 40 / - 5х) - 5
3х²+5х-2 / х² - 4 =
= 3х² + 6х - х - 2 / (х - 2) (х + 2) =
= 3х (х + 2) - (х + 2) / (х - 2) (х + 2) =
= (х + 2)(3х - 1) / (х - 2) (х + 2) =
= (3х - 1) / (х - 2)
Подробное решение во вложении